Insulating coating applied to the surface of aluminum shell of lithium-ion battery core and preparation method thereof

By using an insulating coating composed of liquid polyethylene glycol and nano-level Al2O3-SiO2 composite oxide filler, the problem of easy damage to the surface insulation layer of the aluminum shell of the lithium-ion battery cell is solved, and the insulation and thermal conductivity are taken into account, and the safety performance of the battery is improved.

CN117186734BActive Publication Date: 2025-04-01JINHUA LIANCHUANG PLASTIC POWDER TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311157789.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-04-01
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

The insulating layer on the surface of the aluminum shell of the lithium-ion battery cell is easily scratched by external substances, resulting in insulation failure and affecting the safety performance of the battery.

Method used

An insulating coating composed of liquid polyethylene glycol and nano-scale Al2O3-SiO2 composite oxide filler is used to form a thermally conductive insulating film layer by electrostatic spraying and heating.

Benefits of technology

This insulating coating not only provides good insulation performance, but also has thermal conductivity, stable storage and good leveling effect, which can effectively improve the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117186734B_ABST
    Figure CN117186734B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an insulating coating applied to the surface of an aluminum shell of a lithium ion battery cell. The method comprises the following steps: first, stirring and mixing liquid polyethylene glycol and a nanometer-level Al2O3-SiO2 composite oxide filler; second, adding a curing agent, stirring and dispersing the mixture uniformly; third, adding the mixed material into a high-speed airflow impactor to obtain a nanometer-level filler-curing agent component with a loose spherical structure; fourth, fully and uniformly mixing the components; melt extruding, tableting, crushing, pulverizing, and sieving to obtain an insulating powder coating; and fifth, electrostatic spraying and heating curing, wherein the polyethylene glycol undergoes nucleophilic addition with an epoxy resin around the Al2O3-SiO2 composite oxide under the catalysis of the nanometer-level Al2O3-SiO2 composite oxide, and the epoxy resin and the curing agent undergo cross-linking film-forming reaction to obtain a thermally conductive insulating film layer. The insulating coating obtained by the invention effectively provides insulating performance while taking into account good thermal conductivity, is stable in storage, and has a good leveling effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of insulating coating technology, and in particular to an insulating coating and its preparation method applied to the aluminum shell surface of lithium-ion battery cells. Background Technology

[0002] When lithium-ion batteries are used in practical applications such as electric vehicles, aluminum-cased cells are assembled into pack modules. Patent application CN107706449A discloses a square hard-cased lithium-ion battery and its module. The battery includes a battery casing, cells housed within the casing, and a battery cover sealed to the casing. The battery casing has inwardly recessed first grooves on both sides, and the battery cover has inwardly recessed second grooves on both sides that match the first grooves. When these batteries are arranged side-by-side to form a battery module, the resulting grooved space facilitates the layout of heat dissipation pipes and effectively increases the contact area between individual cells and the heat dissipation system, thereby improving the overall heat dissipation efficiency of the battery module. In existing technologies, the aluminum casing surface is often coated with an insulating layer, which is easily scratched or damaged by external substances or hard particles during production or operation, leading to insulation failure and affecting the battery's safety performance. Summary of the Invention

[0003] The purpose of this invention is to provide a method for preparing an insulating coating for use on the aluminum shell surface of lithium-ion battery cells. The insulating coating obtained by this invention effectively provides insulation performance while also having good thermal conductivity, stable storage, and good leveling effect.

[0004] To solve this technical problem, the technical solution of the present invention is: a method for preparing an insulating coating applied to the surface of an aluminum shell for lithium-ion battery cells, comprising the following steps:

[0005] Step 1: Stir and mix liquid polyethylene glycol and nano-sized Al2O3-SiO2 composite oxide filler. The liquid polyethylene glycol coats and adsorbs into the porous structure of Al2O3-SiO2, resulting in Al2O3-SiO2 composite oxide filler with polyethylene glycol dispersed in it.

[0006] Step 2: Add the curing agent to the mixture obtained in Step 1 and disperse for 5 to 10 minutes, stirring until evenly dispersed;

[0007] Step 3: Add the mixture from Step 2 to a high-speed airflow impactor and solidify it to obtain a nanofiller-curing agent component with a loose spherical structure;

[0008] Step 4: Thoroughly mix the nanofiller-curing agent component, bisphenol A epoxy resin, leveling agent and benzoin obtained in Step 3; melt extrude, press into sheets, crush, pulverize and sieve to obtain insulating powder coating;

[0009] Step 5: The insulating powder coating is electrostatically sprayed onto the aluminum shell surface of the lithium-ion battery cell and cured by heating. Under the catalysis of nano-scale Al2O3-SiO2 composite oxide, polyethylene glycol undergoes nucleophilic addition with the epoxy resin surrounding the Al2O3-SiO2 composite oxide. At the same time, the epoxy resin and the curing agent crosslink to form a film, resulting in a thermally conductive insulating film layer.

[0010] Preferably, the insulating powder coating comprises the following substances in parts by weight:

[0011]

[0012] Preferably, the insulating powder coating further includes an imidazole curing accelerator, wherein the imidazole curing accelerator is present in an amount of 2 to 5 parts by weight; the addition of the imidazole curing accelerator includes the following steps:

[0013] S1. The imidazole curing accelerator is dispersed in deionized water, and the nano-sized Al2O3-SiO2 composite oxide is also dispersed in the imidazole curing accelerator-deionized water dispersion system. The porous structure of the nano-sized Al2O3-SiO2 composite oxide adsorbs the imidazole curing accelerator dissolved in the deionized water to form a load.

[0014] S2. Filter the solids from S1 and vacuum dry at 80°C to 85°C;

[0015] The Al2O3-SiO2 composite oxide loaded with imidazole curing accelerator obtained in S2 is mixed with liquid polyethylene glycol in step one to form a polyethylene glycol coating of the imidazole curing accelerator loaded in the Al2O3-SiO2 composite oxide.

[0016] This invention utilizes the porous nature of Al2O3-SiO2 composite oxides to load imidazole curing accelerators dissolved in water via adsorption. After filtration and drying, the Al2O3-SiO2 composite oxide-imidazole curing accelerator is coated with liquid polyethylene glycol. Due to the liquid nature of polyethylene glycol, it surrounds and adsorbs onto the Al2O3-SiO2 composite oxide, effectively isolating the imidazole curing accelerator from other substances, especially epoxy resin. Imidazole curing accelerators have two nitrogen molecules, located at the secondary and tertiary amine positions, respectively. The active hydrogen of the secondary amine group reacts with the epoxy group below the curing temperature, reacting with the epoxy resin in a chain reaction. Therefore, if the imidazole curing accelerator cannot be effectively separated from the epoxy resin, the leveling time of the resulting insulating powder coating during film formation and curing is greatly shortened, resulting in a rough film layer and hindering the improvement of thermal conductivity.

[0017] The preferred method for preparing the porous Al2O3-SiO2 composite oxide includes the following steps:

[0018] S1. Place the organic template P123, the silicon source tetrabutyl orthosilicate and the aluminum source aluminum nitrate in a nitric acid aqueous solution and stir to mix evenly.

[0019] S2. The precursor was prepared by hydrothermal reaction; the resulting precipitate was washed and dried.

[0020] S3, the precipitate obtained by calcining S2, and the removal of the organic template yield a porous Al2O3-SiO2 composite oxide.

[0021] This invention produces a porous nano-Al2O3-SiO2 composite oxide. On one hand, it effectively loads imidazole curing accelerators, and on the other hand, it utilizes its own solid acid properties to catalyze the addition reaction between polyethylene glycol and epoxy resin during the film-forming and curing process, jointly participating in film formation. The imidazole curing accelerators can only contact the epoxy groups for ring-opening polymerization through the leveling process. Before leveling, due to the presence of polyethylene glycol and the confinement of the pores of the Al2O3-SiO2 composite oxide, it is effectively separated from the epoxy resin. Therefore, the resulting insulating and thermally conductive powder coating has sufficient leveling, and the film is smooth and dense, which is conducive to heat transfer.

[0022] The pH value of the nitric acid aqueous solution in S1 is preferably 3 to 4;

[0023] The molar ratio of silicon to aluminum is (7 to 8):1;

[0024] The mass ratio of P123 to silicon source is 1:(3 to 5). This invention ensures the formation of the resulting pore structure and the structural stability of the filler by controlling the amount of silicon source, aluminum source and organic template.

[0025] The preferred hydrothermal reaction process conditions in S2 are: reaction temperature 105℃ to 130℃; reaction time 10h to 12h.

[0026] The preferred calcination process conditions for S3 are as follows:

[0027] Calcination at 550℃ to 600℃ for 6 to 8 hours.

[0028] This invention effectively removes organic templates, ensuring the support and catalytic effects of the silicon-aluminum composite oxide.

[0029] The preferred process parameters for spraying in step five are as follows:

[0030] Operating voltage 70KV;

[0031] The powder outlet pressure is 0.1 MPa;

[0032] Powder spraying rate: 100g / min;

[0033] Spraying distance: 150 micrometers to 200 micrometers;

[0034] The coating thickness is 150μm.

[0035] The film obtained by this invention is dense, has a smooth surface, and has good thermal conductivity.

[0036] The preferred step of heating and curing is as follows:

[0037] After spraying, let it stand for 2 to 3 minutes;

[0038] The curing temperature is 180℃ to 200℃;

[0039] The curing time is 20 to 25 minutes.

[0040] The preferred hydrothermal reaction process conditions in S2 are: reaction temperature 105℃ to 130℃; reaction time 10h to 12h.

[0041] The preferred calcination process conditions for S3 are as follows:

[0042] Calcination at 550℃ to 600℃ for 6 to 8 hours.

[0043] The preferred process parameters for spraying in step five are as follows:

[0044] Operating voltage 70KV;

[0045] The powder outlet pressure is 0.1 MPa;

[0046] Powder spraying rate: 100g / min;

[0047] Spraying distance: 150 micrometers to 200 micrometers;

[0048] The coating thickness is 130μm to 150μm.

[0049] The preferred step of heating and curing is as follows:

[0050] After spraying, let it stand for 2 to 3 minutes;

[0051] The curing temperature is 180℃ to 200℃;

[0052] The curing time is 20 to 25 minutes.

[0053] The thickness of the coating obtained after curing is 100μm to 120μm.

[0054] Another object of the present invention is to provide an insulating coating for use on the surface of an aluminum shell of a lithium-ion battery cell, prepared by the method of the present invention.

[0055] By adopting the above technical solution, the beneficial effects of the present invention are:

[0056] This invention, following a chronological order, first involves mixing liquid polyethylene glycol (PEG) and nano-sized Al₂O₃-SiO₂ composite oxide filler. The liquid PEG coats and adsorbs into the porous structure of Al₂O₃-SiO₂, resulting in an Al₂O₃-SiO₂ composite oxide filler dispersed with PEG. Then, a curing agent is added to the mixture obtained in step one, and the mixture is dispersed and stirred until homogeneous. High-speed airflow is used to impinge and solidify the mixture, resulting in a nano-filler-curing agent component with a loose spherical structure. This achieves the dispersion and positioning of liquid PEG using both the curing agent and the Al₂O₃-SiO₂ composite oxide. Further, the obtained nano-filler-curing agent component, bisphenol A epoxy resin, imidazole, leveling agent, and benzoin are thoroughly mixed. The mixture is then melt-extruded, pressed into sheets, crushed, pulverized, and sieved to obtain an insulating powder coating. This insulating powder coating is electrostatically sprayed onto the aluminum shell surface of a lithium-ion battery cell and cured by heating. Under the catalysis of the nano-sized Al₂O₃-SiO₂ composite oxide, the PEG reacts with the Al₂O₃-SiO₂ composite oxide. The epoxy resin around the iO2 composite oxide undergoes nucleophilic addition, while the epoxy resin and curing agent crosslink to form a film, resulting in a thermally conductive and insulating film layer.

[0057] After the insulating powder coating melts completely, it begins to flow slowly, forming a thin and smooth layer on the workpiece surface. The components come into contact and undergo a chemical reaction to solidify. In this invention, liquid polyethylene glycol is adsorbed and dispersed in porous Al₂O₃-SiO₂ composite oxides. Al₂O₃-SiO₂ acts as a solid acid catalyzing the ring-opening addition of epoxy and hydroxyl groups, thereby achieving effective connection and contact between the epoxy resin and the porous nanofiller. This effectively promotes the dispersion of the nanofiller and strengthens the connection between the filler and the film-forming substance. The resulting film is dense, and the nanofiller has a large specific surface area, effectively promoting the formation of a thermally conductive network. Compared to existing technologies that use micron-sized fillers or require a combination of multiple filler sizes with a filler mass fraction greater than 40% to ensure the formation of an effective thermally conductive network, which is detrimental to the formation of the film's protective properties or requires a higher overall coating thickness, this invention offers a significant advantage.

[0058] This invention uses porous nano-Al₂O₃-SiO₂ composite oxide as an insulating and thermally conductive filler. It also utilizes alumina to introduce silica, giving the composite oxide solid acid properties and ensuring effective reaction between liquid polyethylene glycol and epoxy resin. This results in a film with good interfacial compatibility with the insulating filler, leading to a dense film. Simultaneously, the nano-insulating filler, aided by the phase composition of liquid polyethylene glycol, promotes relative dispersion between the nano-insulating filler and the solid agent. Increasing steric hindrance during mixing with other components enhances the uniformity of the mixture. After curing, the resulting insulating and thermally conductive coating requires only a thin layer to achieve a high thermal conductivity, while also exhibiting good chemical stability. Attached Figure Description

[0059] Figure 1It is an aluminum casing for a lithium-ion battery cell coated with an insulating coating according to the present invention. Detailed Implementation

[0060] To further explain the technical solution of the present invention, the present invention will be described in detail below through specific embodiments.

[0061] Example 1

[0062] This embodiment discloses a method for preparing porous Al2O3-SiO2 composite oxide, including the following steps:

[0063] S1. Place the organic template P123, the silicon source tetrabutyl orthosilicate and the aluminum source aluminum nitrate in a nitric acid aqueous solution and stir to mix evenly.

[0064] The pH value of the nitric acid aqueous solution in S1 is 3; the molar ratio of silicon to aluminum is 7:1; and the mass ratio of P123 to silicon source is 1:3. This invention ensures the formation of the resulting pore structure and the structural stability of the filler by controlling the amounts of silicon source, aluminum source, and organic template.

[0065] S2. The precursor was prepared by hydrothermal reaction; the resulting precipitate was washed and dried.

[0066] The hydrothermal reaction process conditions in S2 are: reaction temperature 120℃; reaction time 10h.

[0067] S3, the precipitate obtained by calcining S2, and the removal of the organic template yield a porous Al2O3-SiO2 composite oxide.

[0068] The preferred calcination process conditions for S3 are as follows:

[0069] Calcination at 550℃ for 8 hours.

[0070] Example 2

[0071] This embodiment discloses a method for preparing porous Al2O3-SiO2 composite oxide, including the following steps:

[0072] S1. Place the organic template P123, the silicon source tetrabutyl orthosilicate and the aluminum source aluminum nitrate in a nitric acid aqueous solution and stir to mix evenly.

[0073] The pH value of the nitric acid aqueous solution in S1 is 4; the molar ratio of silicon to aluminum is 8:1; and the mass ratio of P123 to silicon source is 1:5. This invention ensures the formation of the resulting pore structure and the structural stability of the filler by controlling the amounts of silicon source, aluminum source, and organic template.

[0074] S2. The precursor was prepared by hydrothermal reaction; the resulting precipitate was washed and dried.

[0075] The hydrothermal reaction process conditions in S2 are: reaction temperature 130℃; reaction time 12h.

[0076] S3, the precipitate obtained by calcining S2, and the removal of the organic template yield a porous Al2O3-SiO2 composite oxide.

[0077] The calcination process conditions in S3 are as follows:

[0078] Calcination at 600℃ for 6 hours.

[0079] In this embodiment, calcination effectively removes the organic template, ensuring the carrier and catalytic effects of the silicon-aluminum composite oxide.

[0080] Table 1 shows the specific surface area and total pore volume of the porous Al2O3-SiO2 composite oxides prepared in Examples 1 and 2. The specific surface area was calculated using the BET method, and the total pore volume was calculated using the BJH method for desorption.

[0081] Table 1. Specific surface area and total pore volume of the Al2O3-SiO2 composite oxides obtained in Examples 1 and 2.

[0082] project Example 1 Example 2 Specific surface area <![CDATA[472m 2 / g]]> <![CDATA[530m 2 / g]]> Total capacity <![CDATA[0.32cm 3 / g]]> <![CDATA[0.38cm 3 / g]]>

[0083] Example 3

[0084] This embodiment discloses a method for preparing an insulating coating for the surface of an aluminum shell of a lithium-ion battery cell, comprising the following steps:

[0085] Step 1: Stir and mix liquid polyethylene glycol and the nano-scale Al2O3-SiO2 composite oxide filler prepared in Example 1. The liquid polyethylene glycol coats and adsorbs into the Al2O3-SiO2 porous structure to obtain Al2O3-SiO2 composite oxide filler with polyethylene glycol dispersed in it. The liquid polyethylene glycol in this example is PEG-200.

[0086] Step 2: Add phthalic anhydride curing agent to the mixture obtained in Step 1 and disperse for 10 minutes, stirring until evenly dispersed;

[0087] Step 3: Add the mixture from Step 2 to a high-speed airflow impactor and solidify it to obtain a nanofiller-curing agent component with a loose spherical structure;

[0088] Step 4: Thoroughly mix the nanofiller-curing agent components, bisphenol A epoxy resin, leveling agent, benzoin, and curing accelerator imidazole obtained in Step 3 according to the amounts in Table 2; in this embodiment, the leveling agent is a polybutyl acrylate leveling agent; melt extrusion, tableting, crushing, pulverizing, and sieving to obtain an insulating powder coating;

[0089] Step 5: The insulating powder coating is electrostatically sprayed onto the aluminum shell surface of the lithium-ion battery cell and cured by heating. Under the catalysis of nano-scale Al2O3-SiO2 composite oxide, polyethylene glycol undergoes nucleophilic addition with the epoxy resin surrounding the Al2O3-SiO2 composite oxide. At the same time, the epoxy resin and the curing agent crosslink to form a film, resulting in a thermally conductive insulating film layer.

[0090] The spraying process parameters in step five are as follows:

[0091] Operating voltage 70KV;

[0092] The powder outlet pressure is 0.1 MPa;

[0093] Powder spraying rate: 100g / min;

[0094] Spraying distance: 150 micrometers to 200 micrometers;

[0095] The coating thickness is 150μm.

[0096] The heating and curing process in step five is as follows:

[0097] After spraying, let it stand for 2 minutes;

[0098] The curing temperature is 200℃.

[0099] The curing time is 25 minutes.

[0100] Example 4

[0101] The main difference between this embodiment and Embodiment 3 is:

[0102] In this embodiment, the liquid polyethylene glycol is PEG-300; the dosage of each component of the insulating powder coating is detailed in Table 2.

[0103] Example 5

[0104] The main difference between this embodiment and embodiment 3 is the amount of each component of the insulating powder coating used, as detailed in Table 2.

[0105] The difference between this embodiment and Embodiment 3 also includes the method by which imidazole, as a curing accelerator, is added to the insulating powder coating:

[0106] In this embodiment, the addition of the curing accelerator includes the following steps:

[0107] S1. The imidazole curing accelerator is dispersed in deionized water, and the nano-sized Al2O3-SiO2 composite oxide is also dispersed in the imidazole curing accelerator-deionized water dispersion system. The porous structure of the nano-sized Al2O3-SiO2 composite oxide adsorbs the imidazole curing accelerator dissolved in the deionized water to form a load.

[0108] S2, filter the solids from S1, and vacuum dry at 80℃;

[0109] The Al2O3-SiO2 composite oxide loaded with imidazole curing accelerator obtained in S2 is mixed with liquid polyethylene glycol in step one to form a polyethylene glycol coating of the imidazole curing accelerator loaded in the Al2O3-SiO2 composite oxide.

[0110] Example 6

[0111] The main difference between this embodiment and embodiment 5 is that the amount of each component of the insulating powder coating is detailed in Table 2, and the method of adding imidazole as a curing accelerator to the insulating powder coating is the same as in embodiment 5.

[0112] Comparative Example 1

[0113] In this comparative example, the filler, phthalic anhydride curing agent, bisphenol A epoxy resin, leveling agent, benzoin, and curing accelerator imidazole are thoroughly mixed according to the amounts in Table 2; in this example, the leveling agent is a polybutyl acrylate leveling agent; melt extrusion, tableting, crushing, pulverizing, and sieving are performed to obtain an insulating powder coating; the filler in this comparative example is alumina with a particle size of 1 to 3 micrometers.

[0114] The insulating powder coating was electrostatically sprayed onto the surface of the aluminum shell of a lithium-ion battery cell, then heated and cured. Simultaneously, the epoxy resin and curing agent crosslinked and reacted to form a film, resulting in a thermally conductive and insulating film layer. The spraying and curing process parameters were the same as in Example 3.

[0115] Table 2. Composition of the insulating powder coatings obtained in Examples 1 to 5 and the comparative examples.

[0116] composition Example 3 Example 4 Example 5 Example 6 Comparative Example 1 filler 70 80 90 75 80 polyethylene glycol 20 30 40 25 / Phthalic anhydride 45 55 65 50 55 Bisphenol A epoxy resin 180 200 220 180 200 Leveling agent 2 3 3 2 3 Benzoin 1 2 2 1 2 Curing accelerator 2 3 4 5 3

[0117] The coatings obtained after curing the insulating powder coatings of Examples 3 to 6 and Comparative Example 1 were subjected to performance tests. The specific test standards and corresponding indicators are detailed in Table 3.

[0118] Table 3 shows the performance indicators of the insulating and thermally conductive coatings obtained in Examples 3 to 6 and Comparative Example 1.

[0119]

[0120]

[0121] The insulation resistance test method in Table 3 is as follows: Apply a 500V DC voltage to the surface of the insulating thermally conductive coating, ground the metal plate, and test the insulation resistance. The impact resistance test refers to GB / T1732. The electrolyte composition used in the electrolyte resistance test is as follows: organic solvents including EC, DMC, and EMC in a volume ratio of 1:1:1; lithium salt of 1 mol / L LiPF6; and additives.

[0122] Based on the data in Tables 1 to 3, it can be seen that, compared with Comparative Example 1, the insulating and thermally conductive coatings obtained in Examples 3 and 4 have good insulation and thermal conductivity properties. At the same time, the film structure is stable, impact-resistant, and has good adhesion. The main reason for the improved performance is that, compared with polyethylene glycol, which utilizes its liquid properties to coat the nano-Al2O3-SiO2 composite oxide with its porous structure, and which can react with epoxy resin under the catalysis of the nano-Al2O3-SiO2 composite oxide, the film layer can effectively ensure dense contact with the nano-Al2O3-SiO2 composite oxide. Furthermore, the nano-Al2O3-SiO2 composite oxide used in this invention has a large specific surface area, which is conducive to the formation of a thermally conductive network. Therefore, the insulation and thermal conductivity are significantly improved compared with Comparative Example 1.

[0123] Compared to Examples 3 and 4, the insulating and thermally conductive coatings obtained in Examples 5 and 6 utilize the adsorption properties of nano-Al2O3-SiO2 composite oxides with porous structures to adsorb imidazole dissolved in water, forming a loading of imidazole. This, combined with encapsulation in liquid polyethylene glycol, effectively surrounds and isolates the imidazole. In other words, imidazole does not contact the epoxy resin during the initial storage and heating of the insulating powder coating. Therefore, the resulting insulating and thermally conductive powder coating exhibits sufficient leveling, a smooth and dense film, and facilitates heat transfer. Thus, as shown in Table 3, this invention loads imidazole onto a nanoporous filler and then encapsulates it with liquid polyethylene glycol. This avoids the reaction of the active hydrogen of the secondary amine group of the imidazole curing accelerator with the epoxy group below the curing temperature, preventing a chain reaction with the epoxy resin. This significantly shortens the leveling time during the film formation and curing process of the resulting insulating powder coating, leading to a rough film layer and hindering thermal conductivity improvement. Therefore, the thermal conductivity and orange peel appearance of Examples 5 and 6 are further improved compared to Examples 3 and 4.

Claims

1. A method for preparing an insulating coating on the surface of an aluminum shell of a lithium-ion battery cell, characterized in that: The following steps are involved: Step 1, stirring and mixing liquid polyethylene glycol and nano-scale Al2O3-SiO2 composite oxide filler, and the liquid polyethylene glycol is coated and adsorbed into the Al2O3-SiO2 porous structure to obtain Al2O3-SiO2 composite oxide filler dispersed with polyethylene glycol; Step 2: Add curing agent to the mixture obtained in step 1 and disperse for 5 to 10 minutes, stirring and dispersing evenly; Step 3, adding the mixed material in step 2 into a high-speed airflow impact machine, and forming and curing to obtain a nano filler-curing agent component with a loose spherical structure; Step 4: fully and uniformly mix the nanofiller-curing agent component, bisphenol A epoxy resin, leveling agent and benzoin obtained in step 3; melt extrude, tablet, crush, grind and sieve to obtain insulating powder coating; The insulating powder coating further comprises an imidazole curing accelerator, wherein the mass fraction of the imidazole curing accelerator is 2 to 5 parts; and the addition of the imidazole curing accelerator comprises the following steps: S1, dispersing the imidazole curing accelerator in deionized water, dispersing the nano-scale Al2O3-SiO2 composite oxide in the imidazole curing accelerator-deionized water dispersion system, and the porous structure of the nano-scale Al2O3-SiO2 composite oxide adsorbs the imidazole curing accelerator dissolved in the deionized water to form a load; S2, filtering the solid obtained in S1, and drying in vacuum at 80°C to 85°C; The Al2O3-SiO2 composite oxide loaded with imidazole curing accelerator obtained in S2 is mixed with liquid polyethylene glycol in the manner of step 1 to form a polyethylene glycol coating on the imidazole curing accelerator loaded in the Al2O3-SiO2 composite oxide; Step 5: The insulating powder coating is electrostatically sprayed on the surface of the aluminum shell of the lithium-ion battery cell and heated to cure. Polyethylene glycol undergoes nucleophilic addition with the epoxy resin around the Al2O3-SiO2 composite oxide under the catalysis of the nano-scale Al2O3-SiO2 composite oxide. At the same time, the epoxy resin and the curing agent undergo cross-linking film-forming reaction to obtain a thermally conductive insulating film layer.

2. The preparation method according to claim 1, characterized in that: The insulating powder coating comprises the following substances in parts by mass: 70 to 90 parts of nano-scale Al2O3-SiO2 composite oxide filler; 20 to 40 parts of polyethylene glycol; 45 to 65 parts of curing agent; 180 to 220 parts of bisphenol A epoxy resin; 2 to 3 parts of leveling agent; 1 to 2 parts of benzoin; The curing agent is a solid acid anhydride curing agent.

3. The preparation method according to claim 1, characterized in that: The preparation method of nano-scale Al2O3-SiO2 composite oxide comprises the following steps: S1, placing the organic template P123, the silicon source tetrabutyl orthosilicate and the aluminum source aluminum nitrate in a nitric acid aqueous solution and stirring to mix evenly; S2, preparing a precursor by hydrothermal reaction; washing and drying the obtained precipitate; S3, calcining the precipitate obtained in S2, removing the organic template, and obtaining a nano-scale Al2O3-SiO2 composite oxide.

4. The preparation method according to claim 3, characterized in that: The pH value of the aqueous nitric acid solution in S1 is 3 to 4; The molar ratio of silicon to aluminum is (7 to 8):1; The mass ratio of P123 to silicon source is 1:(3 to 5).

5. The method for preparing an insulating coating applied to the surface of an aluminum shell of a lithium-ion battery cell according to claim 3, characterized in that: The hydrothermal reaction process conditions in S2 are: reaction temperature 105°C to 130°C; reaction time 10h to 12h.

6. The preparation method according to claim 3, characterized in that: The process conditions for calcination in S3 are as follows: Calcination at 550°C to 600°C for 6 to 8 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The process parameters for spraying in step 5 are as follows: Working voltage 70KV; Powder discharge pressure 0.1MPa; Powder spraying amount: 100g / min; Spraying distance 150 microns to 200 microns; The spraying thickness is 150 μm.

8. The preparation method according to any one of claims 1 to 6, characterized in that: The operation of heating and curing in step 5 is as follows: After spraying, let it stand for 2 to 3 minutes; Curing temperature: 180℃ to 200℃; Curing time: 20min to 25min.

9. An insulating powder coating prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Square hard-shell lithium ion battery and module thereof

    CN107706449A

  • Special insulating powder coating for electro-magnetism line and preparation method thereof

    CN101457117A

  • Thermally conductive composition

    CN101815772A

  • Hierarchically porous silicon-aluminum composite oxide catalytic material and preparation method thereof

    CN106902798A